Ribosomes structure, function, and dynamics - Rodnina, Marina V.; Wintermeyer, Wolfgang; Green, Rachel 1964- (Springer, 2011)
The ribosoeis a macromolecular machine that synthesizes proteins with a high degree of speed and accuracy. Our present understanding of its structure, function and dynamics is the result of six decades of research. This book collects over 40 articles based on the talks presented at the 2010 Ribosome Meeting, held in Orvieto, Italy, covering all facets of the structure and function of the ribosome. New high-resolution crystal structures of functional ribosome complexes and cryo-EM structures of translating ribosomes are presented, while partial reactions of translation are examined in structural and mechanistic detail, featuring translocation as a most dynamic process. Mechanisms of initiation, both in bacterial and eukaryotic systems, translation termination, and novel details of the functions of the respective factors are described. Structure and interactions of the nascent peptide within, and emerging from, the ribosomal peptide exit tunnel are addressed in several articles. Structural and single-molecule studies reveal a picture of the ribosome exhibiting the energy landscape of a processive Brownian machine. The collection provides up-to-date reviews which will serve as a source of essential information for years to come.